Implementing Supply Chain Management In A Manufacturing Environment - Yin, Teo Shu (2002)
In line with the growth of information technology, Supply Chain Management(SCM) has become one of the management tools that has gained much publicity and popularity. SCM allows cross border business transactions and the organization must now be alert to rules and regulations set up by each country for example foreign financial barriers, internet regulations and transborder data transfer.